(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: Physical training is an important area of law enforcement education. Classical training is now supplemented by the transfer of knowledge related to training and lifestyle in law enforcement physical education. The next step is to involve the technical tools in the preparation. The aim of our article is to present the BEMER vascular therapy device and its possible application in the physical training and rehabilitation of law enforcement professionals. Methodology: The effectiveness of the BEMER magnetic therapy device has been demonstrated by clinical research. It is currently used primarily in medicine (improving microcirculation, reducing pain, treating high blood pressure, bone fractures) and sports (warming up, preventing and treating injuries, and enhancing efficiency). In our article, as a method, we present the research found in the literature and related to our topic (the physical training of law enforcement professionals). Findings: Rehabilitation- and measuring devices previously used only in medicine have appeared in our daily lives. Their user-friendly design and safe operation allow anyone to use them under the guidance of a proper professional. We believe that smart devices, including BEMER, have a place in the training of law enforcement professionals. In our article, we present the areas where we consider the use of magnetic therapy effective. Value: In our opinion, BEMER helps to improve the physical performance of law enforcement workers. It is also suitable for rehabilitation after injuries. We recommend using the tool at the National Public Service University, where we could make these treatments available to the students. The direction of our research is the acquisition and use of additional smart devices (smartwatch, body mass meter, chest strap recording physiological data, etc.), which will open new avenues in the field of physical training of law enforcement professionals.